Zarządzanie przez wartość jako metoda wspomagająca tworzenie wartości dla właścicieli przedsiębiorstwa - Wierzbiński, Marcin (Value Based Management as a Method of Aiding Creating Value for Shareholders, 2006)
The article presents one of the recently most popular method of management that aids creating value for shareholders. At the beginning the author points at the reasons for recognizing creating shareholders' value as a main goal of companies. Then there are quoted some of the definitions of value based management. In the main part of the paper there are presented characteristics of value based management stages. As the most important rule in creating shareholders' value the author finds the necessity of keeping continuity between different stages of value based management.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (4); 2006; nr 1119, s. 70-81